2003
DOI: 10.1161/01.cir.0000103664.47406.49
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Progression and Regression of Atherosclerotic Left Main Coronary Artery Disease and Serum Cholesterol Levels as Assessed With Serial Long-Term (≥12 Months) Follow-Up Intravascular Ultrasound

Abstract: Background-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
0
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 40 publications
7
85
0
11
Order By: Relevance
“…This also appears to be the case in humans. [47][48][49][50][51][52][53] Like all animal models of human disease, mouse models of atherosclerosis and lesion regression have several limitations. Importantly, although the mouse appears to be a suitable model for studies of events leading to formation of advanced plaques and even plaque rupture, 54 mice seldom show signs of myocardial infarctions or strokes.…”
Section: Discussionmentioning
confidence: 99%
“…This also appears to be the case in humans. [47][48][49][50][51][52][53] Like all animal models of human disease, mouse models of atherosclerosis and lesion regression have several limitations. Importantly, although the mouse appears to be a suitable model for studies of events leading to formation of advanced plaques and even plaque rupture, 54 mice seldom show signs of myocardial infarctions or strokes.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 107 patients with angiographically insignificant coronary atherosclerosis, left main coronary artery disease detected by IVUS was significantly associated with future coronary events 63 . IVUS studies have shown that the rate of plaque growth in the left main coronary artery correlates with traditional risk factors 64,65 . Patients at greatest risk of cardiovascular events, as determined by the PROCAM, SCORE, and Framingham CVD algorithms, exhibited significantly greater plaque progression between baseline and follow-up (median 14 months).…”
Section: Intravascular Ultrasoundmentioning
confidence: 99%
“…Plainly explained, increased LDL leads to more fatty deposits and formation of platelets in the endothelium of arteries, producing thicker walls and narrowed lu-men of vessels (atherosclerosis) with functional involvement of several organs. Statins reduce LDL, as well as the size of platelets in coronary arteries [2][3][4] . Several studies have been highlighted to show that statins reduce the incidence of coronary artery diseases and cerebrovascular lesions, and improve the survival rate of patients with coronary artery diseases [5][6][7][8] ; benefits can be obtained even in the beginning of the treatment 3 .…”
Section: Hmg-coamentioning
confidence: 99%